Genetic diversity and population structure of Chrysoporthe deuterocubensis isolates from Melastoma and Eucalyptus in Malaysia and Indonesia. Issue 4 (10th August 2022) - Suzuki, Hiroyuki; Marincowitz, Seonju; Wingfield, Brenda D.; Wingfield, Michael J.
Abstract: Chrysoporthe deuterocubensis is the causal agent of a serious canker disease of Eucalyptus spp. in tropical and sub‐tropical areas of Asia. Where the disease occurs, Eucalyptus spp. are non‐native and the native hosts of the pathogen have not been conclusively determined. The chance discovery of C . deuterocubensis on native Melastoma malabathricum growing in the understory of Eucalyptus trees in Indonesia raised the possibility that this woody shrub could be a native host of C . deuterocubensis, which would then have undergone a host jump to Eucalyptus . Four populations of C . deuterocubensis were collected from cankers on Eucalyptus and Melastoma trees in Indonesia and Malaysia. These were subjected to population genetic analyses using microsatellite markers. The genetic diversity for isolates in all four populations was relatively low ( H ¯ = 0.166–0.316) and unlikely to represent a native source. The maximum percentage of genotypic diversity was high for all four populations ( G max = 60.0–71.5%) irrespective of the host. Structure analyses and haplotype networks showed no structure related to the host plant species. Overall, the results failed to provide evidence that the indigenous M . malabathricum is the native host or origin of C . deuterocubensis infections on the Eucalyptus trees studied.